Scenarios of temporal environmental alterations and phytoplankton diversity in a changing bay in the East China Sea - Wang, Yu; Wang, Weibo; Huang, Yaqin; Chang, Lin; Tang, Xiaoming; He, Xuebao; Lin, Hui (Frontiers in Marine Science, 2023)
In the context of global climatic change, the stressors of warming and eutrophication are major stressors that have synergistic significant ecological implications in coastal waters. To In order to investigate examine the diversity of phytoplankton diversity and its association relationship with water quality, we conducted a surveyed of phytoplankton community compositions and their correlation with environmental changes over four seasons in a eutrophic bay of located in the East China Sea. A Through a systematic analysis, we identified diatoms and dinoflagellates as the main primary dominant groups, with the species Skeletonema costatum, Skeletonema marinoi, Biddulphia sinensis, Thalassiosira eccentrica, Leptocylindrus danicus, Coscinodiscus oculus-iridis, Coscinodiscus jonesianus, and Chaetoceros knipowitschi as the most abundant species in all seasons. Significant seasonal alterations were observed among in both environmental settings and phytoplankton species richness, dominance, and abundance. The phytoplankton community varied in its response to diverse aquatic environments and was principally affected by temperature, silicic acid concentrations, and suspended solids. Elevated temperatures favor were found to promote an increase in phytoplankton abundance. However, no clear evidence of Diatom diatom and dinoflagellate succession in related relation to N:P ratio was not evidentobserved across seasons. Water quality analysis illustratedrevealed that most the majority of the study area was exhibited a mid-eutrophic with severe organic pollution. The abundance of phytoplankton was significantly influenced by eutrophication and organic pollutionEutrophication and organic pollution had significant direct effects on phytoplankton abundance. The accelerated warming process related to coastal nuclear power plants and nutrient regime alterations significantly affect the temporal shift of the phytoplankton community. These findings contribute valuable insights into the effects of eutrophic environments on the structure of phytoplankton communities in coastal aquatic systemsThese findings provide further insights into the impacts of eutrophic environments on phytoplankton community structure in coastal aquatic systems.